Workshop Komunikasi Efektif dengan Metode SBAR untuk Peningkatan Sikap Empati Tenaga Kesehatan di RS PKU Muhammadiyah Sampangan - Ayu Rizky Pramestya Merdeka; Yusuf Alam Romadhon (Joong-Ki : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve knowledge, communication skills using the SBAR method (Situation, Background, Assessment, Recommendation), and empathic attitudes of healthcare workers at RS PKU Muhammadiyah Sampangan, Surakarta. Quality health services depend not only on clinical competence but also on interpersonal skills, particularly empathy. The World Health Organization (WHO) states that more than 70% of patient safety incidents result from communication failures. The implementation method was an interactive workshop attended by 30 healthcare workers from various professions, comprising pre-test, interactive material delivery, case simulations, role-play, and post-test. Data normality was assessed using Kolmogorov-Smirnov and Shapiro-Wilk tests; since data were not normally distributed (p < 0.001), the Wilcoxon Signed Rank Test was applied. Results showed a significant increase in mean scores from 8.40 (pre-test) to 9.60 (post-test), with Z = −3.449 and p < 0.001, confirming meaningful improvements in SBAR communication understanding and empathic attitudes. This workshop proved effective as a structured communication intervention model replicable in other healthcare facilities.